2020
DOI: 10.1186/s12885-020-07490-0
|View full text |Cite
|
Sign up to set email alerts
|

Is hypofractionated whole pelvis radiotherapy (WPRT) as well tolerated as conventionally fractionated WPRT in prostate cancer patients? The HOPE trial

Abstract: Background Patients with high-risk prostate cancer are at increased risk of lymph node metastasis and are thought to benefit from whole pelvis radiotherapy (WPRT). There has been recent interest in the use of hypofractionated radiotherapy in treating prostate cancer. However, toxicity and cancer outcomes associated with hypofractionated WPRT are unclear at this time. This phase II study aims to investigate the impact in quality of life associated with hypofractionated WPRT compared to conventionally fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…11 Lastly, the biological dose to the prostate used in POP-RT is sufficient to optimise local control. 11 Indeed, local control plays an important role in optimising progression-free survival and metastasis-free survival, 11,15 and is linked to the dose delivered to the prostate. 24,57 Both the RTOG 9413 and GETUG-01 trials had this issue; 4 taking into account current knowledge, the dose delivered in these two studies was too low to guarantee sufficient local control.…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Lastly, the biological dose to the prostate used in POP-RT is sufficient to optimise local control. 11 Indeed, local control plays an important role in optimising progression-free survival and metastasis-free survival, 11,15 and is linked to the dose delivered to the prostate. 24,57 Both the RTOG 9413 and GETUG-01 trials had this issue; 4 taking into account current knowledge, the dose delivered in these two studies was too low to guarantee sufficient local control.…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
“…24,57 Both the RTOG 9413 and GETUG-01 trials had this issue; 4 taking into account current knowledge, the dose delivered in these two studies was too low to guarantee sufficient local control. Consequently, the rate of local relapse was substantial and led to a second wave of distant metastasis, 15 which diluted the potential benefit of whole pelvis radiotherapy. 1,7,14 Results from Sandler and colleagues 8 confirmed that only when the primary tumour is controlled, whole pelvis radiotherapy might affect the outcome.…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvement of a PCa cure is related to oncological, psychological, and economic issues [ 4 , 5 , 6 ]. Different fractionation schemes for radiation therapy were explored [ 7 , 8 , 9 , 10 ]. Clinical data for low- and intermediate-risk PCa show that treatment outcomes (i.e., genitourinary and gastrointestinal toxicities, biochemical relapse free survival (BRFS), overall survival (OS), and metastases-free survival (MFS)) after ultra-hypofractionated radiation therapy (UF-RT) are similar to conventional-fractionated radiation therapy (CF-RT) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%